Virtual Reality Mindfulness and Personalized Exercise for Patients on Hemodialysis with Depressive Symptoms: A Feasibility Study - Brett T. Burrows; Ashley M. Morgan; Alexis C. King; Rosalba Hernandez; Kenneth R. Wilund (Kidney and Dialysis, 2023)
Nonadherence to exercise-related trials in hemodialysis (HD) patients is a significant burden worldwide. To address this issue, we assessed the feasibility and preliminary efficacy of a combined pre-habilitative virtual-reality-based mindfulness (VRM) program and a personalized activity prescription (PARx) in HD patients with elevated depressive symptoms. Ten HD patients (age = 59.60 ± 13.66) with elevated depressive symptoms completed a 10-week intervention. Participants were randomized into either a VRM+PARx (n = 6) or PARx alone (n = 4) group. During the 2-week prehabilitation, the VRM+PARx group completed our VRM program, while the PARx alone group received usual HD care. Post-prehabilitation, both groups began our 8-week PARx program. Feasibility was assessed by rates of recruitment, retention, adherence, and acceptability and adoption. Preliminary efficacy was measured using metrics of depressive symptoms, mindfulness, fatigue, and physical activity (PA) energy expenditure. A 25% recruitment rate was documented, with 90% retention. A 75% exercise adherence rate was observed and PARx demonstrated high perceived autonomy support (M = 27.6 ± 2.1). Post-prehabilitation, the VRM+PARx group showed significant between-group improvement in mindfulness (p = 0.02) and a significant within-group reduction in depressive symptoms (p = 0.05); however, no difference between groups was observed (p = 0.07). Post-PARx, no between-group difference was evident in PA energy expenditure; however, within the VRM+PARx group, a significant increase in PA energy expenditure was observed (p < 0.01). Fatigue remained unchanged. Our VRM and PARx programs demonstrated feasibility and potential efficacy for HD patients. However, to validate these findings, future trials should consider a larger sample size and a longer duration.